The Influence Of Intensity And Habits Learning On Mathematical Critical Thinking Ability - Purwaningsih, Dian (Study Program of Mathematics Education University of Muhammadiyah Malang, 2018)
The problems often faced by students in the learning process are theability to solve mathematical problems. The process of solvingmathematical problems requires thinking skills. Thinking skills needed toprovide creative ideas in solving mathematical problems include criticalthinking skills. The understanding of students in providing creative ideas isstill low and the ability of students to identify a mathematical problem isstill low. The purpose of this study was to determine the effect of learningintensity on the ability to think critically mathematically, to determine theeffect of learning habits on mathematical critical thinking skills, todetermine the effect of learning intensity and learning habits onmathematical critical thinking skills. This type of research is explanatoryresearch. The results of this study, namely there is a positive influence onlearning intensity on mathematical critical thinking skills, there is a positiveinfluence on learning habits on mathematical critical thinking skills, there isa positive influence on intensity and learning habits on mathematical criticalthinking skills.